Interaction of high-molecular-weight kininogen with endothelial cell binding proteins suPAR, gC1qR and cytokeratin 1 determined by Surface Plasmon Resonance (BiaCore) - Pixley, Robin A.; Espinola, Ricardo G.; Ghebrehiwet, Berhane; Joseph, Kusumam; Kao, Alice; Bdeir, Khalil; Cines, Douglas B.; Colman, Robert W. (Thrombosis and Haemostasis, 2011)
The physiologic activation of the plasma kallikrein-kinin system requires the assembly of its constituents on a cell membrane. High-molecular-weight kininogen (HK) and cleaved HK (HKa) both interact with at least three endothelial cell binding proteins: urokinase plasminogen activator receptor (uPAR), globular C1q receptor (gC1qR,) and cytokeratin 1 (CK1). The affinity of HK and HKa for endothelial cells are KD=7–52 nM. The contribution of each protein is unknown. We examined the direct binding of HK and HKa to the soluble extracellular form of uPAR (suPAR), gC1qR and CK1 using surface plasmon resonance. Each binding protein linked to a CM-5 chip and the association, dissociation and KD (equilibrium constant) were measured. The interaction of HK and HKa with each binding protein was zinc-dependent. The affinity for HK and HKa was gC1qR>CK1>suPAR, indicating that gC1qR is dominant for binding. The affinity for HKa compared to HK was the same for gC1qR, 2.6-fold tighter for CK1 but 53-fold tighter for suPAR. Complex between binding proteins was only observed between gC1qR and CK1 indicating that a binary CK1-gC1qR complex can form independently of kininogen. Although suPAR has the weakest affinity of the three binding proteins, it is the only one that distinguished between HK and HKa. This finding indicates that uPAR may be a key membrane binding protein for differential binding and signalling between the cleaved and uncleaved forms of kininogen. The role of CK1 and gC1qR may be to initially bind HK to the membrane surface before productive cleavage to HKa.
Keywords: Kininogen; surface plasmon resonance; suPAR; gC1qR; cytokeratin 1